1974
DOI: 10.1007/bf00035869
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of paraquat tolerance in Lolium perenne L.

Abstract: Paraquat tolerance has been studied in an experimental population of Lolium perenne. After applying various concentrations of the herbicide, eye assessments of damage were made, and yield responses recorded. There was a quantitative pattern of variation; heritability was studied by analyzing (a) variation within and between families of half-sibs, and (b) the regression of progeny on their female parent. Heritability values were mostly in the range 0.51 to 0.72. It is concluded that it would be possible to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Collectively, segregation analysis of mesotrione resistance at both low and high rates indicated that this resistance is likely multigenic. Herbicide resistance with multigenic inheritance previously has been reported in other weed populations (e.g., Busi et al 2011;Faulkner 1974;Han et al 2014;Neve and Powles 2005).…”
Section: Populationmentioning
confidence: 77%
“…Collectively, segregation analysis of mesotrione resistance at both low and high rates indicated that this resistance is likely multigenic. Herbicide resistance with multigenic inheritance previously has been reported in other weed populations (e.g., Busi et al 2011;Faulkner 1974;Han et al 2014;Neve and Powles 2005).…”
Section: Populationmentioning
confidence: 77%
“…Although there are many reports of differential response to PSI inhibitors in populations of Lolium spp. (Faulkner, 1974;Harvey et al, 1978), the first field-selected case of PSI resistance was not identified until 2002 (Yu et al, 2004).…”
Section: Resistance To Photosystem I Electron Divertersmentioning
confidence: 99%
“…The existence of differences between cultivars suggests that tolerance is heritable and could be increased by selection; this suggestion has recently been confirmed empirically (J. S. Faulkner, unpublished). It is also known that there is heritable variation in the response of perennial ryegrass genotypes to the herbicide paraquat (Faulkner. 1974).…”
Section: Conclusi(hismentioning
confidence: 99%